Poluição sonora por ruído ferroviário em São Carlos e Ibaté-SP: impactos socioambientais e medidas mitigadoras - Grotto, Beatriz de Deus (Universidade Federal de São Carlos, 2022)
This dissertation aims to present the socio-environmental impacts caused by noise pollution, specifically generated by railway noise by the horn of the train that crosses the urban area of São Carlos and Ibaté-SP, thus contributing with substantial data for Civil Inquiries of the Public Ministry, State and Federal, as well as for the formulation of public policies aimed at treating railway noise. In addition, alternative, eradicating or mitigating measures were presented to conciliate the conflict between private companies against public authorities and civil society. This research was exploratory quantitative-qualitative, carried out through three systematic procedures, which will directly answer the three guiding questions: 1. “What is the legislative and technical normative that falls on noise pollution, specifically on railway noise?”; 2. “What are the socio-environmental impacts caused by this noise pollution, especially in the cities of São Carlos and Ibaté-SP?”; 3. “What are the alternatives, mitigating or eradicating measures, for this problem?”. The case study consisted of the analysis of data from a questionnaire applied, in online format, to the populations of São Carlos and Ibate, investigating the damage caused to them by the development of the railway activity. Through this research, it is intended to indicate alternatives for the conciliation of the established conflict, proposing the practice of organizational environmental management through eradicating or mitigating measures for noise pollution by railway noise, based on the data collected and analyzed, and on the study of the Noise Monitoring and Control Program, of the company responsible for the railway activity in question, generating the noise pollution discussed.
Noise pollution by railway noise in São Carlos and Ibaté-SP: socio-environmental impacts and mitigating measures
Keywords: Impacto ambiental; Adequação ambiental; Bem-estar social; Ministério público; Justiça ambiental; Environmental impact; Environmental suitability; Social welfare; Public ministry; Environmental justice; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA DO BEM-ESTAR SOCIAL